O ensino em valores a partir das maneiras e artes de fazer : possibilidades pedagógicas para as aulas de Educação Física - Varnier, Thaise Ramos (2015)
The current time livesa remarkable transformation where the foundations that guide the environment in which we live, including those that form us in, assume a volatile and relative character considering moral values. La Taille e Menin (2009) name this rearrangement of moral principles as "values crisis". As we consider the process of appropriation of values and the context in which they are inserted, we can visualize the school and therefore the Physical Education classes as border posts, hybrid ambients, because it hosts a variety of subjects with different moral principles and values. The objective of this study is to understand the teaching of values worked in the pedagogical practices of Physical Education teachers in the school on text. It is configured as a multi methodological research of exploratory bibliographic feature (GIL, 1987) and qualitative, assuming the narrative (SOUZA, 2008) of research-training type (SOUZA, 2007) as a theoretical and methodological referential. The narratives come from semi structured interviews, iconographic records (images) and bibliographic productions made in a continuing education offered by PROTEORIA. Are contributors of research five teachers of Physical Education, four from the city of Serra and one from Vila Velha, that under the narrative format (auto) biographical explain the pedagogical practices of five teachers of Physical Education. The data show us that, in recent years, under the bias of a axiological relativism, we can find in the teaching practice of scholastic Physical Education na education for education on values, intentionally, anchored in pedagogical specificity of Physical Education.